Prices vs. Quantities in Health Insurance Reimbursement - Francesca Barigozzi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2003)
I compare in-kind reimbursement (which fixes treatment quantities) and reimbursement insurance (which fixes treatment prices) as demandside, cost-containment measures. In the model, illness has a negative impact on labor productivity and public insurance is financed through labor income taxation. Consumers are heterogeneous with respect to intensity of preferences for treatment which is their private information. The social planner may be constrained to adopt uniform (pooling) allocations or may be free to choose discriminating (self selecting) allocations in the reimbursement plan. Analyzing pooling allocations I show that reimbursement insurance dominates in-kind reimbursement from a social welfare point of view. While considering self-selecting allocations I show that the two reimbursement methods are equivalent.
Keywords: 330; Gesetzliche Krankenversicherung; Gesundheitskosten; Adverse Selektion; Theorie; Sachtransfer